1993
DOI: 10.1007/bf01606459
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumour of the thyroid: Clinicopathological, immunohistochemical and ultrastructural study of three cases

Abstract: We describe three cases of solitary fibrous tumour (SFT) arising from thyroid stroma. Grossly, the tumours were clearly delimited but only partly encapsulated. The following histomorphological growth patterns were observed: bundles of cells in storiform configuration; non-structured bundles; prevalence of fibrous matrix; highly cellular, non-structured; prevalence of loose, non-structured extracellular substance; cellular proliferation and vascular spaces in a haemangiopericytic configuration and a lipomatous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 21 publications
3
77
1
2
Order By: Relevance
“…Histologically, all except one case displayed the characteristic lack of architectural pattern and the distinctive cytologic findings. One exceptional case had an extensive lipomatous component [17]. No evidence of local recurrence or distant metastases were reported.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Histologically, all except one case displayed the characteristic lack of architectural pattern and the distinctive cytologic findings. One exceptional case had an extensive lipomatous component [17]. No evidence of local recurrence or distant metastases were reported.…”
Section: Discussionmentioning
confidence: 94%
“…A review of the literature regarding primary thyroid SFT, showed only 19 cases being reported to date ( [7][8][9][10][11][12][13][14][15][16][17] and Table 3). The morphological and immunohistochemical features of SFT of thyroid, including our cases, are identical to pleural-based solitary fibrous tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 40% of cases they are found in subcutaneous tissue; others are located in deep soft tissues of the extremities or extracompartimental in the head and neck region (especially in the orbit), chest wall, mediastinum, pericardium, retroperitoneum and abdnominal cavity region. Other locations, already described, include meninges, spinal cord, periosteum, salivary glands, lungs, thyroid, liver, gastrointestinal tract, adrenal glands, bladder, prostate and testicles (1,2,5,6,(8)(9)(10)(11)13) . Clinically, the patient complains of localized compressive pain.…”
Section: Discussionmentioning
confidence: 95%
“…Pueden presentar degeneración quística. No se ha descrito hemorragia, necrosis ni calcifi cación en ninguno de los casos reportados en tiroides 3,5 . Estos tumores pueden alcanzar un gran tamaño, describiéndose en uno de los casos una masa de 9,7 cm de diámetro 7 .…”
Section: Discussionunclassified